Bai‘ Al-Salam dan Aplikasinya dalam Sistem Pre-Order Online Platform Tanifund - Mujadid, Shofam Amim; Zen, Muhamad (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2025)
This study analyzes the suitability of the digital pre-order system with the bai' al-salam contract from a muamalah jurisprudence perspective, using the TaniFund platform as a model of contemporary practice. In principle, pre-orders share similar characteristics to salam, in that payment is made in advance for goods delivered later according to agreed specifications and timing. However, observations on TaniFund indicate potential Sharia inconsistencies, such as unclear commodity specifications, uncertain harvest times, the risk of product substitution, and possible production delays due to crop failure. Furthermore, the use of conventional protection schemes and the lack of Sharia-compliant dispute resolution mechanisms can give rise to elements of gharar (unclear risk) and injustice for both investors and farmers. This study uses a qualitative-descriptive approach through a study of classical fiqh literature, the DSN-MUI fatwa No. 05/DSN-MUI/IV/2000 on salam, and an analysis of practices on the TaniFund platform. The research results show that pre-orders can be declared valid according to Sharia if they fulfill the pillars and requirements of salam, and are supported by transparent digital mechanisms, written contracts, commodity verification, and Sharia-compliant risk mitigation schemes. Therefore, strengthening contracts, internal regulations, and user education are necessary to ensure that digital pre-order practices, including those at TaniFund, align with the principles of justice, legal certainty, and the welfare of the Islamic economy.